Rancang Bangun Aplikasi Pemantauan Detak Jantung dan Pelacakan Lokasi bagi Penderita Lemah Jantung Berbasis IoT dan Android - Somantri, Somantri; Fergina, Anggun; Maulana, Yosep (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Weak heart is a medical condition that reduces the heart's ability to heat blood throughout the body with optimal efficiency. People with weak heart need regular monitoring regarding their heart condition. Under normal conditions, they should measure the heart rate regularly otherwise a weak heart can lead to serious complications such as acute heart failure or arrhythmias. By using the application, people with heart failure can monitor early signs and symptoms that might indicate complications. The data collected by the application can assist in detecting early changes that are potentially harmful to the patient's health. In this study, the authors designed and developed an IoT and Android-based heart rate monitoring and location tracking system using the prototype method. The prototype method is used in the process of developing this system because it is capable of producing initial prototypes of tools and applications that can be used for testing and validating concepts before carrying out a full implementation. This system consists of two main components, the first is a component of hardware (hardware) and the second is a component of software (software). The hardware used is a pulse sensor that is connected to an Android device via a wireless connection. This sensor is able to detect the patient's heart rate in real-time and send it to the Android device for further processing. In addition, this system is also equipped with a GPS tracking module that allows traveling to the user's location accurately. Software developed using the App Inventor platform. This Android application has an easy-to-use user interface. This application can display real-time heart rate data in graphical form and provide notifications if a significant change is detected in the patient's heart rate. In addition, this application can also display the patient's location on an interactive map. The test results show that this system is capable of monitoring the patient's heart rate with high accuracy and sending data in real-time to an Android device. In addition, tracking the location of the patient's whereabouts was also successfully carried out with an adequate level of precision. This system provides great benefits in monitoring and treating patients with heart failure, enabling medical staff and the patient's family to take quick and appropriate action if there is a significant change in the patient's heart rate or if the patient is in an emergency situation